Pharmacology of boldine: summary of the field and update on recent advances - Sáez, Juan C.; Burrell, Justin C.; Cahill, Catherine M.; Cullen, D. Kacy; Devi, Lakshmi A.; Gilbert, Ryan J.; Graham, Zachary A.; Gurvich, Vadim J.; Havton, Leif A.; Iyengar, Ravi; Khanna, Rajesh; Palermo, Edmund F.; et al. (Frontiers in Pharmacology, 2024)
Over the past decade, boldine, a naturally occurring alkaloid found in several plant species including the Chilean Boldo tree, has garnered attention for its efficacy in rodent models of human disease. Some of the properties that have been attributed to boldine include antioxidant activities, neuroprotective and analgesic actions, hepatoprotective effects, anti-inflammatory actions, cardioprotective effects and anticancer potential.Compelling data now indicates that boldine blocks connexin (Cx) hemichannels (HCs) and that many if not all of its effects in rodent models of injury and disease are due to CxHC blockade. Here we provide an overview of boldine's pharmacological properties, including its efficacy in rodent models of common human injuries and diseases, and of its absorption, distribution, pharmacokinetics, and metabolism.